Enhancement of Phenolic Compounds and Antioxidative Activities by the Combination of Culture Medium and Methyl Jasmonate Elicitation in Hairy Root Cultures of Lactuca indica L. - Yi, Tae Gyu; Park, Yeri; Park, Jai-Eok; Park, Nam Il (SAGE Publications, 2019)
Lactuca indica L. has been traditionally used as a wild vegetable and as a medicinal plant for centuries. The various compounds present in it and their biological activities have been extensively reported. Hairy-root culture combined with agrobacterium-meditated metabolic engineering is a useful technique to achieve stable production of biologically active plant compounds. Here, we evaluated the enhancement of secondary metabolites in L. indica L. and their bioactivities by testing culture media composition and the use of an elicitor. Hairy roots were induced and cultured in MS or SH liquid media for 2 weeks prior to treatment with various concentrations of MeJa, for different periods. The resulting phenolic contents and physiological activities were analyzed. Higher total phenolic, flavonoid, and hydroxycinnamic acids contents were attained by elicitation with MeJa. Metabolite accumulation, especially in SH media and in the presence of MeJa, was time dependent. Particularly, accumulation of chicoric acid increased markedly with time. Similarly, we observed time dependent positive and negative responses of antioxidant activity in DPPH and ABTS assays, respectively. As in previous studies, the highest correlation was found between total phenolic content and total flavonoid content. Further, 3,5-DCQA showed the highest correlation with total phenolic content, total flavonoid content, and antioxidant activities in hydroxycinnamic acids. Our data effectively identified optimal culture conditions to increase the accumulation of secondary metabolites and antioxidant activity in hairy roots cultures of L. indica L.